1994
DOI: 10.1164/ajrccm.149.6.8004327
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of airway structure and function after hyperoxic exposure in immature rats.

Abstract: We have previously demonstrated that hyperoxic exposure (> 95% O2 for 8 d) induces airway cholinergic hyperresponsiveness and remodeling in 21-d-old rats. To examine the potential relationship between airway hyperresponsiveness and remodeling in these animals, we exposed rats to air or hyperoxia for 8 d, returned them to air-breathing, and measured airway responsiveness to inhaled acetylcholine (ACh) and layer thicknesses immediately after or 16 or 48 d after cessation of air or O2 exposure. The ACh concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 19 publications
1
14
1
Order By: Relevance
“…Histopatholo gical analysis of both small and large airways from proximal and distal lung also failed to detect any apparent increase in airway smooth muscle mass. These results differ from those of Hershenson et al (1994), who found airway hyperreactivity in 21-day-old rat pups exposed to >95% oxygen for 7 days. They reported a correlation between the hyperoxia-induced increase in airway hyperreactivity and an accompanying increase in small and medium airway smooth muscle thickness.…”
Section: Discussioncontrasting
confidence: 99%
“…Histopatholo gical analysis of both small and large airways from proximal and distal lung also failed to detect any apparent increase in airway smooth muscle mass. These results differ from those of Hershenson et al (1994), who found airway hyperreactivity in 21-day-old rat pups exposed to >95% oxygen for 7 days. They reported a correlation between the hyperoxia-induced increase in airway hyperreactivity and an accompanying increase in small and medium airway smooth muscle thickness.…”
Section: Discussioncontrasting
confidence: 99%
“…They have demonstrated both recovery of hyperoxia-induced airway remodeling 2 wk after hyperoxia exposure in rat pups and persistence of airway hyperreactivity 9 days after cessation of hyperoxic exposure in neonatal guinea pigs (7,17). Both studies employed exposure to high supplemental oxygen (Ͼ95% and 70%, respectively) and neither study used neonatal mice, confounding comparison to our own data.…”
Section: Discussionmentioning
confidence: 84%
“…From an in vivo perspective, hyperoxiaexposed neonatal rodents have been widely employed to study the pathophysiology of neonatal lung injury. Initial studies focused on the effects of ϳ95% oxygen and documented increased airway reactivity, accompanied by an increase in airway smooth muscle (ASM) layer thickness, both of which resolved several days after cessation of oxygen exposure (7). In contrast, neonatal guinea pigs exposed to 70% oxygen showed a persistent increase in airway response to cholinergic agonist after return to normoxia (17).…”
mentioning
confidence: 99%
“…bronchial smooth muscle; oxygen; hyperoxia; brain-derived neurotrophic factor; tropomyosin related kinase; calcium; substance P PRETERM BIRTH AND NEONATAL lung injury are associated with bronchopulmonary dysplasia (BPD) and a high incidence of childhood asthma (1, 21). While BPD is likely multifactorial in origin, a well-characterized model for BPD is neonatal hyperoxic exposure in rat pups, which is associated with increased cholinergically mediated airway contractile responses in vitro and in vivo (6,24,59). In this regard, neurally mediated bronchoconstriction involves cholinergic mechanisms as well as nonadrenergic/noncholinergic (NANC) pathways (9, 44, 55) mediated via subepithelial C-fiber sensory afferents that release tachykinins [neurokinin A and B and substance P (SP) (19)].…”
mentioning
confidence: 99%